SUSTAINABLE DEVELOPMENT IN INDIA WITH CONSTITUTIONAL PERSPECTIVE (CAHIERS MAGELLANES-NS, 2024)
Although there is little clarity in sustainable development, most attempts to define it involve some mix of equity, the environment, and development. The focus of proponents of sustainable development varies, though, with regards to what needs to be created, what needs to be sustained, how to connect development and environment, and how long these connections should last. The researcher has tried to clarify the concept through the economic, environment & social perspective through its principles and fundamental rights to see it’s implication Constitutionally through doctrinal data analysis.